Perbedaan Tingkat Penerimaan Diri pada Siswa Kelas 7 di SMP Negeri 1 Yogyakarta Dalam Masa Pubertas Ditinjau dari Jenis Kelamin - Margareth Eunike Payangan; Bernardinus Agus Arswimba (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This study aims to find out the difference in self-acceptance rates between students and 7th grade students at SMP Negeri 1 Yogyakarta during puberty. This study also aims to find out the level of self-acceptance in students and students separately. This study uses a comparative quantitative method with 60 students out of a total of 192 students. Data was collected through a Google Form questionnaire containing 47 items based on aspects of self-acceptance according to Hurlock (2004). The reliability of the instrument was tested using Alpha Cronbach with a coefficient of 0.917. The results showed that there was a significant difference in the level of self-acceptance between students and students. Based on data analysis, 20.7% of students are in the medium category, 65.5% in the low category, and 13.8% in the very low category. For female students, 6.5% were in the very high category, 3.2% in the high category, 61.3% in the medium category, 22.6% in the low category, and 6.5% in the very low category. These results are used as the basis for the preparation of social personal guidance topics in the Guidance and Counseling Study Program, Sanata Dharma University, Yogyakarta.